Komunikasi Cultural Resource Management Perang Topat Di Pura dan Kemaliq Lingsar - Aryawati, Ni Made Chandri; Wirawan, I Wayan Ardhi; Wirata, I Wayan (IAHN Gde Pudja Mataram, 2022)
This study aims to conduct a study of the Communication Cultural Resource Management of Topat War at Lingsar Temple Park. This phenomenon is closely related to the public's contribution as a party that plays a role in socio-cultural interaction in an area. Therefore, intercultural communication can be a means used to achieve common goals. There are three problems in this study, namely the form of communication, communication strategies, and the impact of intercultural communication on the implementation of the Topat War Cultural Resource Management in Lingsar. This study uses an interpretive qualitative design of a case study model in order to analyze the communicative events that occurred in the practice of the Topat War holistically as well as to attach the meaning contained in these events. The results of this study found three findings that became the answer to the formulation of the problem, namely, 1) The form of intercultural communication in the application of the Topat War Cultural Resource Management in Lingsar, namely inter-ethnic communication and sub-cultural communication because it includes Balinese Hindu community groups and Sasak Islam Wetu Telu as well as the local government. 2) The communication strategy is carried out by maintaining coordination and communication and trying to increase awareness of the preservation of cultural heritage. 3) The impact of intercultural communication can increase government and public awareness to maintain and manage the site.